Features contamination seed different cereal with S oudemansii Sacc (Experimental biology, 2015)
The specialization and features fruiting on plants - owners S. oudemansii Sacc is investigated for the first time. Thus was of interest to find out, whether the specialization macroconidium of a stage S. oudemansii Sacc from microconidium of a stage differs.
Keywords: fungi S. oudemansii Sacc; family Роасеае; facultative parasites; seed; inoculation; conidium; spore formation